Please help me out!!!!!!!!!!!!!!
![Please help me out class=](https://us-static.z-dn.net/files/daf/715ac51094634fb0866ea5895e6adcb7.png)
Answer: x
Step-by-step explanation:
The shortcut: f⁻¹ and f cancel each other out. So you are left with x
The long way:
f(x) = 47x - 55
f⁻¹(x) is when the x's and y's are swapped and you solve for y
x = 47y - 55
x + 55 = 47y
[tex]\frac{x + 55}{47}[/tex] = y
f⁻¹(x) = [tex]\frac{x + 55}{47}[/tex]
f⁻¹(f(x)) = [tex]\frac{(47x - 55) + 55}{47}[/tex]
= [tex]\frac{47x}{47}[/tex]
= x